2019
DOI: 10.1080/17461391.2019.1631389
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage abnormalities and osteophytes in the fingers of elite sport climbers: An ultrasonography‐based cross‐sectional study

Abstract: The impact of extensive loads on the cartilage of the proximal interphalangeal-(PIP) and distal interphalangeal (DIP) joints of the fingers in elite sport climbers are relatively unknown. The purpose of this study was to investigate the changes in the cartilage of the PIP and DIP joints as well as the existence of osteophytes, in fingers of elite sport climbers with a minimum of 15 years of climbing history. Thirty-one elite male sport climbers and 20 male non-climbers volunteered for the current cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…The finding that DIP joints are more affected by degenerative changes than PIP joints is novel, as previous studies have reported a similar occurrence of osteophytes in both proximal and distal interphalangeal joints ( Allenspach et al, 2011 ; Pastor et al, 2020 ). This finding suggests that at later stages of the career, the DIP joints seem to be more prone to degeneration than the PIP joints.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The finding that DIP joints are more affected by degenerative changes than PIP joints is novel, as previous studies have reported a similar occurrence of osteophytes in both proximal and distal interphalangeal joints ( Allenspach et al, 2011 ; Pastor et al, 2020 ). This finding suggests that at later stages of the career, the DIP joints seem to be more prone to degeneration than the PIP joints.…”
Section: Discussionmentioning
confidence: 80%
“…However, we found most of the clear signs of osteoarthritis in the ap-view in the DIP joints of Dig III. Other studies have also found both fingers, Dig III and IV, to be frequently subject to degeneration ( Allenspach et al, 2011 ; Pastor et al, 2020 ). Therefore, we recommend considering both fingers as particularly affected by degenerative changes in climbers.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The palmar plate (PP) was only displayed in the sagittal plane, and thickness was measured at the PIP as well as the DIP joint between the highest part of the distal middle phalanx and the most convex part of the flexor tendons. All measurement principles for the soft tissue evaluation have been previously described [ 9 , 10 ]. Furthermore, a height- and weight-matched 40-year-old non-climbing male surgeon was evaluated for a direct comparison of the presented pictures.…”
Section: Methodsmentioning
confidence: 99%
“…Endochondral ossification has been considered as the most important process in the formation of osteophytes [15]. The degradation of cartilage is also associated with osteophyte formation [16][17][18]. Our previous study reported that baseline cartilage defects could predict an increase in MRI-detected osteophytes over 2.6 years after adjustment for baseline osteophyte score, BMLs, and meniscal extrusion [19].…”
Section: Introductionmentioning
confidence: 99%